2017
DOI: 10.1016/s1569-9056(17)30958-2
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score analysis of radical cystectomy versus bladder-sparing trimodal therapy in the setting of a multidisciplinary bladder cancer clinic

Abstract: Purpose Multidisciplinary management improves complex treatment decision making in cancer care, but its impact for bladder cancer (BC) has not been documented. Although radical cystectomy (RC) currently is viewed as the standard of care for muscle-invasive bladder cancer (MIBC), radiotherapybased, bladder-sparing trimodal therapy (TMT) that combines transurethral resection of bladder tumor, chemotherapy for radiation sensitization, and external beam radiotherapy has emerged as a valid treatment option. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 6 publications
2
51
0
2
Order By: Relevance
“…Two comparative effectiveness publications also have supported the use and future prospective study of BPT. A Canadian‐based group performed a matched propensity score‐adjusted analysis in a smaller cohort (112 patients), and demonstrated comparable 5‐year disease‐specific survival rates in the RC (73.2%) and trimodal BPT (76.6%) cohorts …”
Section: Discussionmentioning
confidence: 99%
“…Two comparative effectiveness publications also have supported the use and future prospective study of BPT. A Canadian‐based group performed a matched propensity score‐adjusted analysis in a smaller cohort (112 patients), and demonstrated comparable 5‐year disease‐specific survival rates in the RC (73.2%) and trimodal BPT (76.6%) cohorts …”
Section: Discussionmentioning
confidence: 99%
“…RC entails high risk of re‐operations, long hospital‐stays, long‐term sequelae, and even postoperative mortality . A contemporary bladder‐sparing treatment alternative to RC is chemoradiotherapy . There is no evidence from randomized controlled trials to support superiority of RC over radiotherapy with respect to survival.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder-sparing strategies for patients with MIBC have been explored to overcome these innate limitations of RC. Supported by a growing body of evidence, multimodal bladder-sparing therapy has recently been acknowledged as an important treatment option along with RC [6][7][8][9][10][11][12][13][14]. Most of the currently existing protocols for bladder preservation are trimodal therapies, which comprise maximal transurethral resection of bladder tumour (TURBT) and chemoradiotherapy (CRT) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Supported by a growing body of evidence, multimodal bladder-sparing therapy has recently been acknowledged as an important treatment option along with RC [6][7][8][9][10][11][12][13][14]. Most of the currently existing protocols for bladder preservation are trimodal therapies, which comprise maximal transurethral resection of bladder tumour (TURBT) and chemoradiotherapy (CRT) [10][11][12][13][14]. Recently the published literature has shown that trimodal bladder-sparing therapy yields survival outcomes similar to those of RC [12]; however, a significant number of patients experienced MIBC recurrences in the preserved bladders after receiving trimodal bladder-sparing therapy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%